ZAKAT DAN PAJAK DALAM BINGKAI KESEJAHTERAAN SOSIAL - Zulaikha, Siti (STAIN Jurai Siwo Metro, 2012)
AbstrakZakat (Almsgiving) and tax are the two institutions which have a sosial function in the welfare of the people. Each one has a different instrument in realizing these functions. Zakat is an obligation of religion, and the tax is the duty of the state. There are basic similarities between zakat and taxation that is the element of coercion, the element manager, and the destination. Purpose of both is inseparable from the above functions, particularly in terms of financing the construction of the state to create public welfare. The welfare of society can be achieved if the management of zakat and taxes done professionally and trustful. The problem is bad management so that both management objectives have not been able to achieve welfare justice.Kata Kunci: Zakat, pajak, dan Kesejahteraan